Can a simple echocardiographic Doppler VTI based flow comparison between the RVOT and LVOT assist in identifying patients with a significant atrial septal defect?. (3rd October 2022) - Khav, N; Cheng, K; Ramkumar, S; Nerlekar, N; Mottram, P; Nicholls, S; Moir, S
Abstract: Background: Detection of haemodynamically significant shunting from atrial septal defect (ASD) can be identified by using the pulmonary-systemic flow ratio (Qp/Qs). However, calculation of Qp/Qs by echocardiography relies on geometric assumptions that outflow tracts are circular, suffers from squared linear measures, and accurate measurement of right ventricular outflow tract (RVOT) diameter is challenging. Whilst adults with ASD should have overt right ventricular dilatation, RV sizing on echocardiography is often subjective and underappreciated. We evaluated whether a dimensionless index of flow (VTI) differences between the RVOT and left ventricular outflow tract (LVOT) could assist in identifying patients with ASD, and compared it with relative atrial index (RAI), a parameter previously assessed in identifying atrial shunting. Methods: Data from 64 consecutive patients who underwent ASD closure and had no concomitant lesions, were compared with 63 normal controls. RVOT VTI, LVOT VTI, LVOT diameter, and atrial areas were measured. Results: Between controls and ASD patients, there was no difference in LVOT VTI or forward stroke volume, but ASD patients had significantly higher RVOT VTI. The RVOT-LVOT VTI ratio was 1:1 in controls and 1.5:1 in ASD patients. Area under the ROC curve analysis of RVOT-LVOT VTI ratio was 0.83, and a ratio of 1.1:1 predicted patients with ASD with 86% sensitivity and 73% specificity. In comparison, the area under the ROC curve analysis of RAI was 0.70, and an RAI of 1.05:1 predicted patients with ASD with 77% sensitivity and 44% specificity. Conclusion: Calculation of the dimensionless RVOT-LVOT VTI ratio is simple, and may be a useful additional semi-quantitative tool to assist cardiologists and sonographers in detecting atrial shunting, particularly in patients with borderline or overt right heart dilatation, and identify who patients should undergo further evaluation. Funding Acknowledgement: Type of funding sources: None.